Stereomicroscopic analysis of dental materials employed in endodontic exposed to high temperatures - Aramburo, Johanna; Zapata, Angela; Zúñiga, Sugey; Moreno, Freddy (Revista Estomatología, 2011)
Objective: To describe the physical estereomicroscopical changes that occur in dental tissues and materials employed in a conventional endodontic treatment after application of high temperatures.Materials and methods: An in Vitro study was carried out to observe microscopic, structural and physical changes on hard dental tissues (enamel, dentine and cement) and on endodontic materials (gutta-percha Maillefer Dentsply®, endodontical cement based on oxide of zinc-eugenol Eufar®, cement based on epoxic resin Top Seal® Dentsply®, glass ionomer Fuji I® GC America®, silver amalgam GS80® SDI® and composite Point 4® Kerr®) in 124 human teeth, submitted to five temperature ranks (200ºC, 400ºC, 600ºC, 800ºC, 1000ºC).Results: The studied tissues and dental materials presented great resistance to the high temperatures without varying considerably their micro structure, such as that the physical changes (dimensional stability, cracks, pits, fractures, texture, color, carbonization and incineration) can be observed through estereomicrophotographies and can be associated to each specific rank of temperature.Conclusions: Some macrostructural changes of dental tissues and the dental materials occur of specific form in each rank of temperature, and for this reason they can be employed in the comparison before and postmortem during the process of identification of burned or charred corpse and human remains.Key words: Forensic dentistry, human identification, stereomicroscopy, dental materials, high temperatures.